Trends in Sciences Reaches Its Highest-Ever CiteScore: 2.4 in 2025 - Channuie, Phongpichit (Trends in Sciences, 2026)
It is with immense pride and enthusiasm that we announce another extraordinary achievement for Trends in Sciences (TiS). According to the latest Scopus journal metrics released in June 2026, the journal has attained a 2025 CiteScore of 2.4, representing the highest CiteScore in our history and marking yet another significant step in our journey toward academic excellence. Our latest performance indicators clearly demonstrate the journal’s rapid growth, increasing scholarly influence, and expanding global visibility: CiteScore 2025: 2.4 (up from 1.8 in 2024 and 1.2 in 2023) Scopus Percentile: 66th Percentile in the Multidisciplinary category Journal Quartile: Securely positioned in Quartile 2 (Q2) The progression of our CiteScore over recent years tells a compelling story of sustained development. From 0.8 in 2022 to 1.2 in 2023 [1], 1.8 in 2024 [2], and now 2.4 in 2025, the journal has achieved an impressive threefold increase in citation impact within just three years. Notably, the rise from 1.2 to 2.4 over the past two years represents a remarkable 100% growth, reflecting the increasing recognition, discoverability, and scholarly value of the research published in Trends in Sciences. This consistent upward trajectory is not merely a numerical accomplishment; it is evidence of a strong and sustainable academic ecosystem built upon rigorous editorial standards, ethical publishing practices, and a robust peer-review process. The achievement further strengthens our position as a leading international multidisciplinary journal and reinforces our standing as one of the highest-performing multidisciplinary journals published in Thailand. Most importantly, this success belongs entirely to our community. Every citation, every published article, and every milestone achieved is the result of the collective efforts of our authors, reviewers, editorial board members, and readers. We extend our deepest gratitude to our authors for entrusting us with their innovative and impactful research, to our reviewers for their expertise and dedication in maintaining scientific quality, and to our editorial team for their unwavering commitment to excellence. As we look toward the future, we remain committed to further enhancing the quality, visibility, and international impact of the journal. Building upon the momentum of this achievement, we will continue to strengthen our editorial processes, expand our global network of authors and reviewers, and invest in innovative digital strategies that improve the accessibility and dissemination of scientific knowledge worldwide. The 2025 CiteScore of 2.4 is far more than a metric – it reflects the trust that the global scientific community places in Trends in Sciences. We are deeply grateful for your continued support and partnership, and we warmly welcome your future contributions as we strive together toward even greater achievements.